PENGARUH PEMAHAMAN STANDAR AKUNTANSI PEMERINTAHAN DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN: STUDI EMPIRIS PADA PEMERINTAH KOTA SIBOLGA - Hamonangan Siallagan (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2022)
This study aims to analyze the effect of understanding government accounting standards (SAP) and utilization of information technology on the quality of local government financial reports, either partially or simultaneously. The population in this study are Civil Servants who work in 26 Regional Organizations (OPD) in Sibolga City. The sampling technique was purposive sampling with the following criteria: Financial Administration Coordinator, Treasurer and Property Manager and a sample as much as 78. The data used in the form of primary data obtained through the distribution of questionnaires directly to the OPD in Sibola City. By using multiple linear regression analysis techniques, evidence is obtained that the understanding of government accounting standards and the use of information technology has a positive and significant effect on the quality of local government financial reports. The implication is that the government must improve the understanding of understanding government accounting standards and the use of information technology so that the quality of financial reports can improve.